Cytoreductive surgery and hyperthermic intraperitoneal chemotherapy with oxaliplatin for peritoneal mesothelioma: Preliminary results and survival analysis. (March 2015) - Hubert, Julien; Thiboutot, Eva; Dubé, Pierre; Cloutier, Alexis-Simon; Drolet, Pierre; Sideris, Lucas
Abstract Background Peritoneal mesothelioma is a rare disease with poor prognosis. The present study reports single center experience with cytoreductive surgery (CRS) and hyperthermic intraperitoneal chemotherapy with oxaliplatin (HIPEC-OX) over an eight-year period. Methods Prospectively collected data of all consecutive patients with epithelial or multicystic peritoneal mesothelioma from August 2004 to October 2012 was analyzed. Patients with sarcomatoid or biphasic peritoneal mesothelioma were not included due to general poor prognosis. Treatment consisted in CRS and HIPEC-OX (460 mg/m2) at 43 °C during 30 min. For statistical analysis, Kaplan–Meier survival curves were plotted and compared using log-rank tests. Cox proportional-hazards regression model was used to analyze the influence of different variables on survival. Results Nineteen patients with peritoneal mesothelioma underwent laparotomy with CRS and HIPEC-OX with curative intent (15 epithelial, and 4 multicystic). Mean follow-up was 36.7 months. The estimated one-year and three-year overall survival rates were respectively 100% and 91%. The estimated one-year and three-year disease-free survival rates were respectively 77% and 50%. Complications were graded according to the Clavien-Dindo classification [1] and major complications occurred in 57% of cases. There was no postoperative mortality. Histological grade was not a prognostic factor of disease-free survival (p = 0.37). Conclusion When comparing survival results as well as morbidity-mortality rates, the present study shows that CRS and HIPEC-OX is a valid treatment for peritoneal mesothelioma.